2013
DOI: 10.1002/jnm.1915
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modeling of static hysteresis loop using variable parameters

Abstract: The application of the Jiles–Atherton (J–A) hysteresis model for numerical modeling of measured quasistatic hysteresis loops of non‐oriented soft magnetic material is investigated. The J–A model used assumes its parameters are dependent on actual effective magnetic field strength. This is carried out by using a new parameter associated with the mathematical description of the J–A model. In this paper, the author demonstrates that these varying parameters and the proposed algorithm of parameter estimation are u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Using the same values of model parameters modeling was carried for a lower induction amplitude, B m = 0.6 T. As already stated, in the present paper we assumed that the values of all model parameters were kept fixed. However, it should be remarked that in the past a lot of research on the JA model was devoted to examination of model accuracy for lower excitation levels, to mention as representative examples References [40,[58][59][60]. In the above-mentioned references the necessity to update some values of model parameters upon the excitation amplitude is raised and different functional relationships are proposed as a method to improve the model accuracy.…”
Section: Measurements Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same values of model parameters modeling was carried for a lower induction amplitude, B m = 0.6 T. As already stated, in the present paper we assumed that the values of all model parameters were kept fixed. However, it should be remarked that in the past a lot of research on the JA model was devoted to examination of model accuracy for lower excitation levels, to mention as representative examples References [40,[58][59][60]. In the above-mentioned references the necessity to update some values of model parameters upon the excitation amplitude is raised and different functional relationships are proposed as a method to improve the model accuracy.…”
Section: Measurements Modelingmentioning
confidence: 99%
“…mention as representative examples References [40,[58][59][60]. In the above-mentioned references the necessity to update some values of model parameters upon the excitation amplitude is raised and different functional relationships are proposed as a method to improve the model accuracy.…”
Section: Measurements Modelingmentioning
confidence: 99%
“…For an isotropic magnetic material, the parameters of the JA model are scalars. However, experience has shown that a single set of parameters produces inaccurate results if used to fit all the symmetric minor BH loops [28]. Thus, in this paper, the parameters of the JA model are estimated for each measured symmetric minor BH loops.…”
Section: ∂Mmentioning
confidence: 99%
“…The classical Langevin and Brillouin functions are commonly used to represent the anhysteretic magnetic characteristics [7], [28]. However, these functions, or their combinations, cannot always fit with the measurements [29].…”
Section: Anhysteretic Characteristicmentioning
confidence: 99%
See 1 more Smart Citation